Studi Empiris: Pengaruh Kualitas Kerja Terhadap Kinerja Pegawai Pada Kantor Kecamatan Baki Kabupaten Sukoharjo - Youra Putri Anindari; Khabib Alia Akhmad; Agus Suyatno (CV. KAMPUS AKADEMIK PUBLISING, 2024)
. This research aims to find out whether organizational culture, work environment and work ethic can influence employee performance. The respondents for this research were 50 sub-district office employees. Data was collected using a questionnaire and analyzed using the SmartPLS 3.0 program with an outer model to assess validity and reliability, and an inner model to see the predictive power of the structural model. The results of research based on calculations using SEM-PLS show that organizational culture has a positive and not significant influence on employee performance, the work environment has a positive and significant influence on employee performance, work ethic has a positive and significant influence on employee performance, organizational culture, work environment and work ethic have an influence Positive and Simultaneous on Employee Performance.